1988
DOI: 10.3382/ps.0671725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethoxyquin Feed Preservative and Peroxide Level on Broiler Performance

Abstract: Rancidity development in feeds and feed ingredients reduces the feeds' nutritive value and produces toxic peroxides. This investigation was conducted to determine the effects of different levels of peroxide on broiler performance and to determine the effectiveness of ethoxyquin in ameliorating the adverse effects of peroxides. Poultry fat was oxidized to contain 0, 50, 100, and 175 meq peroxide/kg and added to diets to provide 0, 2, 4, or 7 meq peroxide/kg feed, respectively. Liquid ethoxyquin was incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1
13

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 11 publications
6
40
1
13
Order By: Relevance
“…Dibner et al (1996) obtained similar results, while Calabotta and Shermer (1985) and Cabel et al (1988) reported otherwise. The smaller differences in feed utilisation found in our experiment than in the final body weight of turkeys indicate that the main factor lowering gain of the birds was decreased consumption of feed containing oxidized fat.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Dibner et al (1996) obtained similar results, while Calabotta and Shermer (1985) and Cabel et al (1988) reported otherwise. The smaller differences in feed utilisation found in our experiment than in the final body weight of turkeys indicate that the main factor lowering gain of the birds was decreased consumption of feed containing oxidized fat.…”
Section: Resultssupporting
confidence: 74%
“…In the experiment of Calabotta and Shermer (1985) lower body weight of chickens was found when the birds were fed a diet with a low content of peroxides, from 1 to 2 mEq 0 2 /kg. In the experiment of Cabel et al (1988) the body weight of 49-day-old chickens was lower only in the group receiving the highest amount of peroxides (7 mE 0 2 /kg). In the study by Dibner et al (1996) the body weight of 3-week old chickens fed diets containing 4 mEq 0 2 /kg, was not significantly lower than in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations